Penerapan Metode Ulrich dalam Perancangan Konsep Desain Mesin Pengepres Kaleng dengan Menggunakan Lead screw - Abdulloh Sami Alfaris; Rizal Indrawan, S.ST., M.T.; Agus Khumaidi (Proceedings Conference On Design Manufacture Engineering And Its Application, 2023)
The development of the beverage industry is increasing, in the handling and management of canned waste there is still a manual process, by stepping on or hitting cans with tools so that the volume of cans shrinks. Therefore, an idea and innovation is needed to design and make a machine as a tool for pressing cans in the form of a small-scale can pressing machine. The process of making the machine uses the Ulrich method. Identification of machine needs to concept selection and design embodiment. Based on the results of the design with the Ulrich method, design concept 2 was selected. Has a relative value for rate of 28% and for weight score of 31%.